Variation of Molar Conductance Under Isodielectric Condition: A Qualitative Study - Ishwara Bhat, J.; Susha, C.B. (Asian Journal of Chemistry, 2010)
A qualitative study of effect of isodielectric constant on the molar conductance of chloramine-B (CAB) as a function of temperature is undertaken. Reported molar conductance at infinite dilution for chloramine-B obtained by Debye-Hückel-Onsager, Kraus-Bray and Shedlovsky conductivity model are considered in the study. It has been proposed that ion-solvation, i.e., ion-solvent and solventsolvent interaction, the solvent molecular size, its viscosity and other related physical property of the solvent in presence of water are taking major role in molar conductance study keeping effect of dielectric constant as a subsidiary factor.